The factors related to medication adherence in outpatient hypertension patients at Leuwiliang Hospital, Bogor Regency - Nurita Andayani; Luthfiah Ratikasari; Rira Noviarianti; Manninda, Reise; Fauzi, Hamid (Pharmaciana, 2025)
Hypertension is the leading cause of cardiovascular disease in the world and contributes to 10 million deaths every year. Non-adherence is an important factor in uncontrolled hypertension, thus leading to reasons for non-adherence to treatment or medication. This study aims to identify the factors related to adherence to treatment for outpatients at Leuwiliang Regional Hospital, Bogor Regency. This study used a quantitative descriptive approach with cross-sectional data. The study population consisted of all outpatient hypertension patients at Leuwiliang Regional Hospital in 2023. Sampling used the purposive sampling technique with a sample of 312 patients. Data were analyzed descriptively and analytically with the Spearman-rho correlation test. The results showed that the level of adherence among patients with hypertension was mostly moderate (39.7%). Treatment adherence was related to self-motivation (p-value = 0.000), but the relationship was weak, with a correlation coefficient of r = 0.258. The level of knowledge, family support, and role of health workers did not have a significant relationship to the level of adherence. The correlation value between the level of knowledge and the level of adherence had a negative relationship, although it was not significant. These might be due to knowledge, family support, and the role of health workers might not directly influence the level of compliance but might be supported by other variables such as age, gender, education, patient access to health facilities, patient economic level, length of hypertension, economic profile, and patient hypertension level (length of hypertension), but in this study no relationship analysis was carried out.